Trypanosoma congolense: B-Lymphocyte responses differ between trypanotolerant and trypanosusceptible cattle - Taylor, K.A.; Lutje, V.; Kennedy, D.; Authié, Edith; Boulange, A.F.; Logan-Henfrey, L.L.; Gichuki, B.; Gettinby, George (Elsevier, 1996)
Trypanosomiasis is a serious constraint to livestock production in sub-Saharan Africa. Some breeds of cattle are genetically more resistant to the pathogenic effects of trypanosome infection. We measured B-cell activation and the quantity and isotype of antibody produced at the cellular level in six trypanotolerant N'Dama and five trypanosuceptible Boran cattle. The frequencies of spleen cells secreting total and parasite-specific IgM and IgG were measured prior to and 16.28 and 35 days after a primary challenge with Trypanosoma congolense. Boran cattle had higher frequencies of splenic cells secreting IgM specific for trypanosome-derived variable surface glycoprotein (VSG), cysteine protease (congopain CP) and heat shock protein (hsp70/BiP) and the nonparasite antigen, ovalbumin, than did N'Dama cattle. In contrast, the number of VSG-specific IgG-secreting cells was significantly greater in N'Dama than in Boran cattle. During infection low titers of anti-BSG IgM were detected in blood than Boran during infection. The peripheral blood mononuclear cell population of N'Dama cattle contained a higher percentage of surface IgM-positive B-cells prior to and throughout infection than were found in the blood of Boran. In addition during infection N'Dama cattle had more circulating lymphocytes that could be activated in vitro to undergo differentiation into IgM- and IgG-secreting cells. These findings demonstrate differences in the frequency of trypanosome-specific antibody-secreting cells in the spleen and in the activation state of B-cells in the blood between N'Dama and Boran cattle during a primary infection with T. congolense.